Formulasi Dan Pembuatan Sabun Mandi Herbal Eco Enzyme Sebagai Antiseptik Alami - Muhammad Tahir (Jurnal Kesehatan Yamasi Makassar, 2025)
This study aimed to develop herbal bath soap formulations based on eco enzyme and evaluate their physical characteristics according to SNI quality standards. The soap was formulated using the Cold Process method with three formula variations: F0, F1, and F2. The pH test results showed that all formulas were within the range of 9.03–9.05, meeting the SNI standard. The moisture content test showed the lowest value in F0 and the highest in F2, all of which were within the SNI standard. The total fat of the formulas ranged from 45.005% to 52.815%, meeting the maximum limit of the SNI. The free alkali values of all formulas ranged from 0.0095% to 0.0949%, in accordance with the SNI standard. Formula F2 was considered the best formulation because it produced soap with optimal physical characteristics and met all standard parameters. Eco enzyme has been proven effective as an active ingredient with potential antifungal, antibacterial, and natural cleansing properties in herbal bath soap formulations.